2022
DOI: 10.1038/s41598-022-05866-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated physiological, proteomic, and metabolomic analyses of pecan cultivar ‘Pawnee’ adaptation to salt stress

Abstract: The pecan is a salt-alkali-tolerant plant, and its fruit and wood have high economic value. This study aimed to explore the molecular mechanisms responsible for salt stress tolerance in the pecan grown under hydroponic conditions to simulate salt stress. The results showed that the photosynthetic rate (Pn) was reduced in response to salt stress, while the intercellular carbon dioxide concentrations (Ci) increased. The response of the pecan to salt stress was measured using iTRAQ (isobaric tags for relative or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In the present study, SOA showed that carbohydrate metabolism and translation were the most affected biological process subcategories for differentially expressed genes and proteins, respectively. In addition to being a substrate for energy production, carbohydrates play a role in plant stress perception and signal transduction and can also mediate osmotic regulation and carbohydrate distribution [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, SOA showed that carbohydrate metabolism and translation were the most affected biological process subcategories for differentially expressed genes and proteins, respectively. In addition to being a substrate for energy production, carbohydrates play a role in plant stress perception and signal transduction and can also mediate osmotic regulation and carbohydrate distribution [21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that AtFXG1 modifies xyloglucan oligosaccharides through the hydrolysis of t-fucosyl residues [ 41 ]. Furthermore, our group’s previous analysis concluded that the up-regulation of L-fucose accumulation is a critical feature of pecans’ metabolic regulatory network under salt stress [ 30 ]. CilGDSL42.57 , which is homologous to AtFXG1 , exhibits the largest expression change in response to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, HemI 1.0.3.7 software (http://hemi.biocuckoo.org/down.php, accessed on 20 August 2021) was used to generate the gene expression heatmaps based on the qRT-PCR data. Additionally, as previously reported [30], the protein extracts of pecan leaves were used to isobaric tags for relative and absolute quantitation (iTRAQ) analysis. To undertake a functional annotation analysis of the DEPs selected for GDSLs, we used the NCBI website (https://www.ncbi.nlm.nih.gov/, accessed on 9 November 2021).…”
Section: Analysis Of Gdsl Expression Profiles Using Qrt-pcr and Isoba...mentioning
confidence: 99%
“…Post-translation modifications, such as protein phosphorylation, promote changes in those proteins that already existed in the cells before the onset of the stress and play roles important in plant resistance to abiotic stresses [ 24 , 25 ]. Carbohydrate metabolism also plays a role in plant stress perception and signal transduction, besides being a substrate for energy production and a mediator of osmotic regulation and carbohydrate distribution [ 26 ].…”
Section: Discussionmentioning
confidence: 99%